DevelopmentUser Interface and Experience of Web-Based Psychological Tests (Case Study: Universal University) - Roza, Yuni; Maesaroh, Siti (Journal Collabits, 2024)
Developing a user interface and user experience for a web-based psychological test application at Universal University, especially the Uvers Career Center (UCC), is a technology that is needed to make the appearance of an application non-monotonous and dynamic. Previously, psychological test applications that had been developed by previous research did not meet the UCC's own standard requirements. The data source that will be used is qualitative data and uses a usability testing method with the aim of making it easier for users to carry out psychological tests with a display that is in accordance with what is required by the UCC. The final result of the research is designing the user interface and experience of the MindQuiz application which has a usability score of 83.11.